2021
DOI: 10.3390/pharmaceutics13081180
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Nasal Application of Cyclodextrins: Excipients and/or Actives?

Abstract: Cyclodextrins (CDs) are oligosaccharides widely used in the pharmaceutical field. In this review, a detailed examination of the literature of the last two decades has been made to understand the role of CDs in nasal drug delivery systems. In nasal formulations, CDs are used as pharmaceutical excipients, as solubilizers and absorption promoters, and as active ingredients due to their several biological activities (antiviral, antiparasitic, anti-atherosclerotic, and neuroprotective). The use of CDs in nasal form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 102 publications
1
9
0
Order By: Relevance
“…Cytotoxicity measurement revealed that the noncytotoxic concentrations are 1.03 mg/mL HPβCD_MEL-P_PVA_spd and 0.38 mg/mL αCD_MEL-P_PVA_spd. These results corresponded to the literature data, where a higher tolerable concentration was detected for HPβCD than αCD [46]. LPS was not cytotoxic to the cells.…”
Section: In Vitro Cytotoxicity and Il-6 Cox-2 Il-1b Expressionsupporting
confidence: 92%
“…Cytotoxicity measurement revealed that the noncytotoxic concentrations are 1.03 mg/mL HPβCD_MEL-P_PVA_spd and 0.38 mg/mL αCD_MEL-P_PVA_spd. These results corresponded to the literature data, where a higher tolerable concentration was detected for HPβCD than αCD [46]. LPS was not cytotoxic to the cells.…”
Section: In Vitro Cytotoxicity and Il-6 Cox-2 Il-1b Expressionsupporting
confidence: 92%
“…The formation of inclusion complexes with organic molecules, which can be included wholly or partially in the hydrophobic cavity, is favored by this conformation. CD complexation can be exploited, primarily to enhance the guest's solubility but also to ameliorate other properties of the drug such as chemical stability, to prevent adverse side effects (e.g., gastrointestinal irritation), to mask unpleasant odors and flavors, and to prevent drug interactions with other components of the formulation (e.g., drug, active molecule and excipients) [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Cyclodextrins are cyclic compounds composed of D-glucose molecules connected by 1,4-glycosidic bonds; they are water-soluble, non-reducing, molecules that take the form of a white crystalline powder ( Rassu et al, 2021 ). Commonly used α-, β-, and γ-cyclodextrins are composed of six, seven, and eight glucose molecules, respectively ( Papakyriakopoulou et al, 2021 ).…”
Section: Methods To Improve Brain-targeted Nasal Mucosal Drug Deliver...mentioning
confidence: 99%